Optimalisasi Ekstraksi Karotenoid Dengan Menggunakan Berbagai Jenis Pelarut Organik - anggreini, riski ayu (Program Studi Teknologi Pangan, 2018)
Color is one of factors that determine the quality of a food product, however it turns out that not all dyes are safe for consumption. The use of non-food grade synthetic dyes such as textile dyes and leather can be a long-term risk to health. Likuala palm fruit is considered to be a potential source of natural dyes because it has a carotenoids content. However, the type of suitable solvent for obtaining carotenoids extraction is still unknown, so the purpose of this study was to determine the right type of solvent for the extraction of carotenoids color in Licuala palm fruit peel. There are 2 stages in this research, color extraction of Likuala palm fruit and analysis color stability. The analysis carried out was color intensity, total carotenoids (mg/100ml) and yield (%). The results showed that extraction using hexane solvent: acetone with a ratio of 50:50 was able to extract color with intensity, total carotenoid (mg / 100 ml) and the highest yield (%)